The Parallelization of Computations for Ensuring Information Security in Connected Vehicle Systems Using Q-Effective Programming: The Example of Dijkstra's Algorithm - Sokolov, Mikhail P.; Manatin, Pavel A.; Zyulyarkina, Natalya D. (2023 International Russian Smart Industry Conference (SmartIndustryCon), 2023)
This work researches the possibility of applying the concept of a Q-determinant for the parallelization of calculations in the implementation of algorithms to ensure the security of information in systems of connected vehicles. The increasing complexity of connected vehicle systems increases the computational complexity of algorithms used to identify vulnerable nodes in such systems. This requires finding an effective approach to the parallelization of calculations. As an example, Dijkstra's algorithm is used to search for vulnerable nodes in a network of connected vehicles. The method of designing effective programs based on a Q-determinant concept is described. The results of an experimental study of the developed programs conducted on the "Tornado SUSU" supercomputer are presented. The research makes it possible to conclude that a Q-determinant concept is an effective approach to parallelizing Dijkstra's algorithm.